A Study of the Level of Students’ Understanding of their Own Emotions Within the Structure of Emotional Intelligence as an Important Component of their Professional Preparation - Zaritskaya, V. V. (Psychological Prospects Journal, 2011)
The level of students’ understanding of their own emotions within the structure of emotional intelligence as an important component of their professional preparation is analyzed in the article.